(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the legal aspects of ensuring the rights and interests of women and girls in our country, creating suitable working and living conditions for them, realization of their abilities and potential, raising their socio-political status and prestige, development of legislation in their social protection.